Rancang Bangun Alat Pendeteksi Kondisi Cuaca Kota Balikpapan Menggunakan Global Navigation Satellite System (GNSS) Wind Turbine - Endrawati, Budiani Fitria; Yusphie, Adhe; Putri, Arum Prastiyo; A, Azam Fadhil; R, Mohammad Saiful; Robiandi, Fadli (LPPM ITK, 2018)
Balikpapan is one of the cities in East Kalimantan with unique characteristic of the region. The characteristics of the region and the height of the area from the sea surface of the city of Balikpapan is one of the factors, therefore need to be designed a tool to detect weather especially in Balikpapan city. The device design using Global Navigation Satellite System (GNSS) Wind Turbine. The measurement results are based on temperature, humidity and wind speed. From the measurement of temperature, humidity and wind speed obtained an average of 30.97oC; 73.49% and 2.91 m/s. According to method World Meteorological Organization,  temperature, humidity and wind speed data is accepted.